Association of Famine Exposure on the Changing Clinical Phenotypes of Primary Hyperparathyroidism in 20 years - Yuan, Tian-jiao; Yang, Yu-ying; Zhu, Min-ting; He, Yang; Zhao, Lin; Zhou, Wen-zhong; Su, Ting-wei; Zhao, Hong-yan; Sun, Li-hao; Tao, Bei; Liu, Jian-min (Frontiers in Endocrinology, 2022)
Background & Aims: Primary hyperparathyroidism(PHPT) has been evolving into a milder asymptomatic disease. No study has assessed the association between famine exposure and such a shift. We aim to explore the effects of China’s Great Famine exposure on the changing pattern of PHPT phenotypes. Methods: 750 PHPT patients diagnosed from 2000 to 2019 were studied. The clinical presentations were compared between them in recent 10 years (2010-2019) and previous 10 years (2000-2009). Participants were then categorized into fetal, childhood, adolescent，adult exposure, and unexposed groups. Logistic regression was used to estimate the odds ratios (ORs) and confidence intervals (CIs) of famine exposure as factors contributing to the changes in the clinical presentations of PHPT. Results: Serum levels of PTH, albumin-corrected Ca，tumor size，eGFR，BMDs (all P<0.001)，and clinical symptoms became milder in recent 10 years. Famine exposure (72.6% vs 58.4%，P<0.001), especially the adult exposure (18.8% vs 4.1% , P<0.001)was significant less in recent 10 years. The ORs (95%CIs) of having upper 3rd tertile PTH were 2.79(1.34,5.8), 2.07(1.04,4.11), 3.10(1.15,8.38) and 8.85(2.56,30.56) for patients with fetal, childhood, adolescent and adult famine exposure, respectively. The ORs (95%CIs) of upper 3rd tertile albumin-corrected Ca and upper 3rd tertile of tumor size was 4.78(1.39, 16.38) and 4.07(1.12,14.84) for participants with adult famine exposure, respectively. All these associations were independent of age, sex, disease duration and other confounders. Conclusions: The clinical manifestations of PHPT in China continue to be milder. Exposure to famine is associated with PHPT. Less famine exposure might be responsible for the mile form of PHPT in recent years.